Solar collector installations combined with heat substations = Instalacje kolektorów słonecznych współpracujące z węzłami ciepłowniczymi - Ziembicki, Piotr; Bernasiński, Jan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the concept of combined heat production in solar collector installations supporting heat substations. In the first part, the systems of storing solar energy and typical solutions used in the integration of collectors with local gas sources of heat are discussed. Further on, the concept of technological solutions for heat substations using various forms of accumulating solar energy are presented.
Keywords: kolektory słoneczne; węzły ciepłownicze; magazynowanie energii; źródła energii odnawialnej; solar collector; heat substations; energy storage; sources of renewable energy